Highly Sensitive Detection of IDH2 Mutations in Acute Myeloid Leukemia - Petiti, Jessica (J Clin Med, 2020)
Background: Acute myeloid leukemia is a heterogeneous hematological disease, characterized by karyotypic and molecular alterations. Mutations in IDH2 have a role in diagnosis and as a minimal residue disease marker. Often the variant allele frequency during follow up is less than 20%, which represents the limit of detection of Sanger sequencing. Therefore, the development of sensitive methodologies to identify IDH2 mutations might help to monitor patients’ response to therapy. We compared three different methods to identify and monitor IDH2 mutations in patients’ specimens. Methods: Performances of PNA-PCR clamping, droplet digital PCR and Sanger for IDH2 status identification were evaluated and compared in 96 DNA patients’ specimens. Results: In contrast with Sanger sequencing, our results highlighted the concordance between PNA clamping and digital PCR. Furthermore, PNA-PCR clamping was able to detect more mutated DNA with respect to Sanger sequencing that showed several false negatives independently from the allelic frequency. Conclusions: We found that PNA-PCR clamping and digital PCR identified IDH2 mutations in DNA samples with comparable results in a percentage significantly higher compared to Sanger sequencing. PNA-PCR clamping can be used even in laboratories not equipped for sophisticated analyses, decreasing cost and time for IDH2 characterization.